Biomonitoring of heavy metals using Usnea antarctica lichens (extended abstract) - Zvěřina, O.; Coufalík, P. (Pavel); Barták, M.; Komárek, J. (2016)
Present study was designed to investigate the contents of selected heavy metals in the Usnea antarctica lichens from James Ross Island (JRI), Antarctica. A knowledge of current levels of heavy metals is essential for monitoring of increasing pollutant burden of the Antarctic environment.